INFLUENCE OF FLUOROCARBON COMPOUNDS ON ANTI-FRICTION AND OPPOSITE PROPERTIES OF TRICOMPOUNDS - Leusenko, Darya (Problems of Friction and Wear, 2024)
The results of the study of the influence of fluorocarbon compounds of the type (СХ)n on the antifriction and antiwear properties of tribocompounds are presented. It is shown that in conditions of extreme lubrication of gears and bearings, these compounds have good prospects for use as additives and additives to oils. Mechanisms of lubricating action and some examples of practical application are considered. The developed methods of using carbonofluorides include running-in of friction nodes in environments that contain carbonofluorides, introduction of carbonofluoride additives in oils, plastic lubricants, lubricating-cooling and hydraulic fluids. Approbation of these methods in friction nodes of gas turbine engines (GTD) showed the prospect of their wide use in aviation technology. The most important results of the test are that in the presence of carbonofluorides, the service life and maximum allowable contact stresses of rolling bearings and gears can be significantly increased, and after the introduction of carbonofluorides, the friction nodes become less sensitive to the quality of lubricants.